Measuring Employee Work Stress Level on Cyberloafing Behavior - Danang Wikan Carito; Suwignnyo Widagdo; Muhaimin Dimyati (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
The drastic increase in the use of information technology ranging from computers, laptops and smartphones tends to allow for a wide-scale transformation in human life. Coupled with a very big change, namely the emergence of the internet in the midst of society, where all information can be presented according to the needs of its users, and users are no longer limited by age, especially from educational and work backgrounds. The purpose of this research is to find a solution to the problem which will later provide an overview and empirical evidence of the problem of cyberloafing behavior carried out by employees of the Village Government Office in Lumajang Regency. The data collection technique in this research questionnaire is to use an online questionnaire to 80 respondents at the Village Government Office in Lumajang Regency. Management of data in this study using the help of the IBM SPSS Statistics Version 24 program. The analysis used is multiple linear regression analysis. The results showed that: 1) role conflict had a significant effect on cyberloafing behavior, 2) role ambiguity had no significant effect on cyberloafing behavior, 3) role overload had no significant effect on cyberloafing behavior.